2010
DOI: 10.1016/j.ins.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Attribute selection with fuzzy decision reducts

Abstract: Rough set theory provides a methodology for data analysis based on the approximation of concepts in information systems. It revolves around the notion of discernibility: the ability to distinguish between objects, based on their attribute values. It allows to infer data dependencies that are useful in the fields of feature selection and decision model construction. In many cases, however, it is more natural, and more effective, to consider a gradual notion of discernibility. Therefore, within the context of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(89 citation statements)
references
References 64 publications
(63 reference statements)
0
89
0
Order By: Relevance
“…For K x ∈ Cov(C) it holds that K x (x) = 1, so we have that Future work includes the study of fuzzy extensions of the loose pair of covering based rough set model, as well as the research of new fuzzy covering based rough set models. Moreover, we are interested in the applicability of fuzzy covering based rough sets in feature selection [18].…”
Section: Interrelationships Between Fuzzy Extensions Ofmentioning
confidence: 99%
“…For K x ∈ Cov(C) it holds that K x (x) = 1, so we have that Future work includes the study of fuzzy extensions of the loose pair of covering based rough set model, as well as the research of new fuzzy covering based rough set models. Moreover, we are interested in the applicability of fuzzy covering based rough sets in feature selection [18].…”
Section: Interrelationships Between Fuzzy Extensions Ofmentioning
confidence: 99%
“…Both models use aggregation operators instead of the inf-and sup-operator and preliminary work showed that they have interesting theoretical and practical assets. Unfortunately, they do not satisfy the inclusion property, which is required if we want the approximations to be on both sides of the set to be approximated, and is important for feature selection [8].…”
Section: Introductionmentioning
confidence: 99%
“…The method that we develop is a wrapper. Although many researchers have focused on developing fuzzy rough feature selection [11] algorithms, there is not much literature on fuzzy rough PS yet. Nevertheless, fuzzy rough set theory [12] is a good tool to model noisy data.…”
Section: Introductionmentioning
confidence: 99%